Coexistence of sarcoidosis and Hashimoto thyroiditis - H. Semiz; M. Yalcin; S.V. Kobak (PAGEPress Publications, 2018)
Sarcoidosis is a chronic, inflammatory disease with unknown cause characterized by non-caseating granuloma formations. It can present with bilateral hilar lymphadenopathy, skin lesions, eye involvement and locomotor system findings. Hashimoto thyroiditis is an organ-specific autoimmune disease characterized by increased autoantibody synthesis. Sarcoidosis can involve different endocrine glands. Thyroid gland involvement may lead to increased thyroid function disorders and autoantibodies. Herein, we report an 80-year-old female patient with sarcoidosis and Hashimoto coexistence.